Binge-Eating Disorder: A Primer for Professional Counselors. Issue 1 (1st January 2016) - Miller, Raissa M.; McManus, Jaime D.
Abstract : Binge-Eating Disorder (BED) is a primary diagnosis listed in the Feeding and Eating Disorders chapter of the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5; American Psychiatric Association [APA], 2013). Although BED is considered one of the most common eating disorders, symptoms often go unrecognized and untreated (Striegel-Moore et al. 2010). In this article, BED criteria are reviewed and guidelines for assessment, diagnosis, and treatment are offered. A case study is also provided to illustrate the application of BED utilizing best practices.